A descriptive study on the compliance of patients treated in the UPCD to the maintenance phase of periodontal therapy - Antonio, Marina Pilar V.
Forty-two patients who received periodontal therapy from the UPCD between 1995 and 1997 were interviewed in order to determine their level of compliance to the maintenance phase of periodontal therapy. In addition, it is also the objectives of this study to find the reasons for poor compliance and to establish a relationship between compliance levels and age, gender, civil status, educational attainment, social status, smoking, oral hygiene, disease diagnosis, or treatment mode. The findings were that none of the subjects were perfectly compliant. Ten (24%) were found to be Erratically Compliant, having attended 60-99% of the recommended number of maintenance visits. Fourteen (33%) were Erratically Compliant 2, having attended 1-59% of the recommended visits. Eighteen (43%) were totally Non-Compliant. The foremost reason for their poor compliance was a lack of time due to conflicts with their work schedules. No relationship could be established between compliance ratings and age, civil status, initial disease diagnosis, flossing, smoking and socioeconomic status. On the other hand, a correlation was established with time lapse prior to initial maintenance visit (0.56 Spearman Rho). If a patient does not return for treatment within 15 months, he or she is not likely to return for treatment at all. There was an increasing number of subjects with increased tooth brushing frequency among higher compliance levels. There was an increasing number of subjects with higher educational attainment among higher compliance levels.